Exposure to Pornographic Media Among Adolescents Aged (20-24 Years) - Meilin Maulita; Fenny Etrawati; Nurhidayah Nasution (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Exposure to pornographic media among adolescents has become an increasingly concerning issue. High curiosity and technological advancements elevate the risk of adolescents being exposed to pornography. The aim of this study is to determine the exposure to pornographic media among university-level adolescents aged 20-24 years. This study used a quantitative approach with cross-sectional design. This study used secondary data from Nurhidayah Nasution in 2019. The research activities were conducted at Universitas Muhammadiyah Palembang, South Sumatra, in September 2019. There were 140 teenagers ages 20 to 24 involved in this study which were selected using cluster sampling technique. Data processing was conducted through stages of checking for missing data, editing, coding, and tabulating. Data were analysed univariately, bivariately using the chi-square test, and multivariately using logistic regression tests with predictive models. The results of the analysis show that 39.3% of adolescents are exposed to pornography. There is a significant relationship between gender (p=0.003, PR=2.518, 95% CI (1.306-4.855)), peer behavior (p=0.000, PR=4.000, 95% CI (2.456-6.514)), peer norms (p=0.000, PR=2.441, 95% CI (1.549-3.846)), and lifestyle (p=0.012, PR=1.747, 95% CI (1.160-2.633)) with exposure to pornographic media among adolescents. Exposure to pornographic media is 8.7 times more likely to occur in adolescents with peers exhibiting negative behaviors after being controlled for the confounding variable of peer norms (p=0.000, PR=8.742, 95% CI (3.375-20.342)). As a result, a comprehensive approach is needed through supervision and education involving parents and cross-sectoral government to improve self-control and supervision on digital literacy so that adolescents can filter information wisely and avoid exposure to pornographic media. Keyword: Adolescent, Media, Pornography